Telecommunications interception in Turkey: Rights to privacy vs. discourses of security - (:unkn) unknown (IGI Global, 2010)
The paper discusses telecommunication interceptions in Turkey as a state surveilling itself as well as its citizens. While surveillance of state officials including the judiciary indicates a perception of threat from inside the state, these perceptions overlap with the 'deep state' phenomenon in Turkey. Despite the 2005 legal reforms which introduce strict legal standards for communications surveillance, current political developments reveal that wiretapping remains as a commonly used micro-power application. The paper, by utilizing Foucault's theory, aims to uncover the 'conditions of possibility' for the use of this disciplinary technique in Turkey with a certain focus on the actual power relations and discourses of truth. © 2011, IGI Global.